Juice processing [ quality, safety and value-added opportunities - Falguera, Victor; Ibarz, Albert (Boca Raton, Florida : CRC Press, 2014)
The ability to provide quality juices that contain proper vitamins and nutritional components strongly depends on the processes fruits undergo during the various stages of industrial manufacturing. New technologies have been developed to help ensure the production of quality juices without neglecting safety. Covering both new approaches to traditional issues and innovative processes, Juice Processing: Quality, Safety and Value-Added Opportunities addresses various aspects of fruit juice processing and other issues related to the use of by-products generated in this industry
Includes index
Keywords: Fruit juices